Data supporting: 'State of Charge Estimation of Lithium Sulfur Batteries using Sliding Mode Observer' - Munisamy, Srinivasan; Wu, Wenxuan (Cranfield University, 2022)
Data set used for paper titled 'State of Charge Estimation of Lithium Sulfur Batteries using Sliding Mode Observer'.
Keywords: Sliding mode observer'; 'State of Charge'; 'battery management systems'; 'Lithium Sulfur Batteries Lithium sulfur batteries'; 'Extended Kalman Filter'